Pengaruh Digital Marketing, Diskon, Dan Brand Image Terhadap Penjualan: Studi Literature Pada Pasar E-Commerce - chandra prayoga; Dheo Rimbano; Ranita kusuma; Destia aldari; Sundari; Nopendra spio (CV. ITTC INDONESIA, 2025)
This article aims to determine how Digital Marketing, Discounts and Brand Image affect Sales in E-Commerce. The research question in this study is whether Digital Marketing, Discounts and Brand Image affect sales in E-Commerce. This study uses the Systematic Literature Review (SLR) method which comes from research journals that have been published in Google Scholar ranging from 2019 to 2024. The results of the study state that Digital Marketing affects sales in the E-Commerce market, Discounts affect sales in E-Commerce, and Brand Image affects sales in E-Commerce.